Analysis of student's geometry reasoning ability at senior high school - Ayuningtyas, W; Mardiyana; Pramudya, I (Journal of physics. Conference series, 2019)
Each student possesses different levels of reasoning. This difference depends on students' reasoning ability such as observing patterns, formulating conjecture, testing conjecture, constructing arguments, and describing logical conclusions. This study aims to analyze students' reasoning ability. The students' reasoning analysis ability play significant role assisting the teachers to improve students' reasoning, especially in geometric reasoning ability. This study is a qualitative descriptive research on students of high school level. The subjects used in this study were 30 students of grade XI. The results showed that students' geometrical reasoning abilities were still relatively low. Students remains having difficulties in understanding of how to formulate guesses, establish and assess mathematical arguments, and draw logical conclusions about some ideas and their relevance. The average student has difficulty in determining the size of the ribs based on properties of the geometry. Students also find it difficult to provide explanations / arguments regarding the related relationships between the constructs.